Computational Fluid Dynamics Simulation of Airflow in the Normal Nasal Cavity and Paranasal Sinuses - Xiong, Guan-Xia; Zhan, Jie-Min; Jiang, Hong-Yan; Li, Jian-Feng; Rong, Liang-Wan; Xu, Gen (American journal of rhinology, 2008)
This study aimed to investigate airflow velocity, trace, distribution, and air pressure, as well as the airflow exchange between the nasal cavity and paranasal sinus in a normal subject using computational fluid dynamics. Fluent software is used to simulate nasal cavity and paranasal sinus structure after CT scanning of a normal adult subject. Airflow velocity, pressure, distribution, and trace lines were calculated by Navier-Stokes equation and numerically visualized. Airflow in the common and middle meatus accounted for >50 and 30% of total nasal cavity flow. Flow velocity was maximal in the common meatus, followed by the middle meatus. Flow velocity and flux in each paranasal sinus was extremely low. The flow trace in the inferior and lower part of the common meatus was predominately straight in form. Flow was parabolic in the middle and superior meatus and the middle and upper parts of the common meatus. Air pressure was high at the front end of the inferior and middle turbinate and the uncinate process. There was little pressure difference/flow exchange between inner and outer aspects of the paranasal sinus. The major airflow forms are straight (lower common and inferior meatus) and parabolic (middle and upper common meatus and middle superior). Flow force is strongest at the front end of the inferior and middle turbinate and uncinate process. There is very little exchange between the paranasal sinus and the nasal cavity during stable airflow.